Exploration of breast motion under different activities and intensities - Jiazhen Chen; Yin ChingDoris Keung; Yue Sun; Joanne Yip; Kit-Lun Yick (Journal of Engineered Fibers and Fabrics, 2025)
This study systematically investigates breast motion dynamics during running, jumping rope, and high knee skips to inform sports bra design. Using motion capture, researchers analyzed three-dimensional breast movement. MATLAB analysis revealed distinct displacement patterns: running showed an irregular horizontal figure-eight trajectory, jumping rope had a vertically elongated path, and high knee skipping resembled a butterfly shape. Under braless condition, high knee skipping resulted in the greatest breast displacement, with notable superior-inferior (68.54–74.89 mm) and medial-lateral (47.02–65.99 mm) movements, while jumping rope showed notable superior-inferior (47.88–63.69 mm) but minimal medial-lateral (9.08–14.05 mm) displacement. Running had the least superior-inferior displacement (9.73–36.61 mm) but considerable medial-lateral movement (15.72–49.17 mm). Running’s medial-lateral displacement is 1.5 times superior-inferior; jumping rope’s superior-inferior is five times medial-lateral; high knee skipping is balanced at 0.8 times superior-inferior. Higher exercise intensities increased breast motion, most prominently in running. High knee skipping generated the highest breast accelerations up to (medial-lateral: 1.52 g ; superior-inferior: 4.18 g ), while jumping rope (medial-lateral: 0.48 g ; superior-inferior: 4.06 g ) and running (medial-lateral: 1.1 g ; superior-inferior: 2.65 g ) followed. Displacement and acceleration wearing low-support and high-support sports bras were also examined. Sports bras should offer activity-specific support: medial-lateral for running, superior-inferior for jumping rope, and multidirectional for high knee skipping, with adjustability.